Results of a literature review on methods for estimating buildings energy demand at district level. (15th May 2019) - Ferrari, Simone; Zagarella, Federica; Caputo, Paola; D'Amico, Antonino
Abstract: In the framework of distributed energy planning, evaluating reliable energy profiles of different sectors has a prominent role. At the same time, it is a quite challenging task, since the availability of actual energy profiles of buildings at the district level is not widespread. A survey of over 70 studies in scientific literature has been accomplished and a set of criteria has been defined for classifying the selected contributions based on the energy demand data features, source and/or estimation methods, highlighting the ones adopting hourly energy profiles. As final results, tables summarizing the main methods characteristics and a selection of studies providing directly useable energy profiles are reported. Therefore, this study could be useful for stakeholders involved in energy simulations of buildings stocks and community energy planning in assessing the buildings energy demand, with different desired level of detail and available data. The research, broadly, demonstrates that the potential replicability of analysed methods is constrained to the datasets availability and, particularly, highlights the need of reliable hourly energy profiles definition for developing accurate energy scenarios. Highlights: A review of over 70 studies focussing on urban buildings energy demand is presented. A set of criteria for classifying the selected studies is defined. The selected studies are classified by estimation method and time resolution. Tables on methods' features and on studies with useable energy profiles are provided. The review can support stakeholders involved in assessing buildings energy demand.